2010
DOI: 10.5551/jat.4564
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Procedural Platelet Reactivity After Clopidogrel Loading in Korean Patients Undergoing Scheduled Percutaneous Coronary Intervention

Abstract: mol/L ADP-induced PRmax were 64% and 75%, respectively. P2Y12 reaction unit (PRU) was 274 76, and 69.8% (n 150) showed PRU ≥ 240. A carrier of at least one CYP2C19 variant allele showed higher PRs than non-carriers. In multivariate regression analysis, carriage of the CYP2C19 variant allele ( 2 or 3) was determined to be a significant predictor of HPPR (odds ratio 4.202, 95% confidence interval 1.996 to 8.850, p 0.001). Conclusions: Korean patients undergoing scheduled PCI cannot achieve adequate pre-procedura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 50 publications
1
12
1
Order By: Relevance
“…Previous reports, such as genome-wide association studies, demonstrated that the antiplatelet effect of clopidogrel is mostly influenced by the CYP2C19 genotype 11,16) ; however, the genotyping of CYP2C19 cannot precisely predict the antiplatelet effect of clopidogrel. Some EM and IM patients can sometimes be poor responders in a real clinical setting 8,15) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports, such as genome-wide association studies, demonstrated that the antiplatelet effect of clopidogrel is mostly influenced by the CYP2C19 genotype 11,16) ; however, the genotyping of CYP2C19 cannot precisely predict the antiplatelet effect of clopidogrel. Some EM and IM patients can sometimes be poor responders in a real clinical setting 8,15) .…”
Section: Discussionmentioning
confidence: 99%
“…Patients are classified by CYP2C19 enzymatic activities into 3 groups, extensive metabolizer (EM) ( 1/ 1; wild type), intermediate metabolizer (IM) ( 1/ 2 or 1/ 3), and poor metabolizer (PM) ( 2/ 2, 3/ 3, or 2/ 3). Notably, the frequency of PMs is higher in Asians (-20%) than Caucasians (3-5%) [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by us 9) and others 10) examined the antiplatelet effects of clopidogrel in Japanese patients and detected clear effects related to CYP2C19 SNPs. The percentage of people lacking enzymatic activity, designated as poor metabolizers (PM), is 3-5% in Western populations, while approximately 20% in Asians, including Japanese 11,12) ; therefore, CYP2C19 SNPs have a bigger impact on Asians 13) , including Japanese. It is well known that antiplatelet therapy increases the risk of bleeding complications.…”
Section: Ppi Studymentioning
confidence: 99%
“…This effect has been observed with loading dose regimens of 300, 600 mg and higher, and maintenance dosing of 75 and 150 mg [8,20,[28][29][30][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. While increased dosing reduces the number of patients with high residual platelet reactivity, not all patients reach an optimal level of platelet inhibition even with higher dosing.…”
Section: E V I D E N C E O F G E N E T I C I M P a C T O N T H I E N mentioning
confidence: 99%